Physical Fitness and Functional Ability of Children with Intellectual Disability: Effects of a Short-Term Daily Treadmill Intervention - Meir Lotan; Eli Isakov; Shlomo Kessel; Joav Merrick (The Scientific World Journal)
Persons with intellectual disability (ID) and associated multiple disabilities have been found by many researchers to be a population with deficient physical fitness measures, which can be explained by an inactive lifestyle, a result of lack of awareness of the positive physical effects of physical exercise, or lack of motivation for any motor activity. Various plans for physical exercise have been put forward, but many are found impractical in nonresearch-based intervention. In this study, 15 children with ID on a motor functioning level of 7—14 months used a treadmill daily for 2 months. Our findings indicated a most significant improvement in the level of physical fitness of the participants (p < 0.005), as measured by pulse at rest and during effort. The improvement in physical fitness modestly (r = 0.5), but significantly (p < 0.05), correlated with a significant (p < 0.0007) improvement in functional ability of the participating children. Further examination a year after intervention terminated showed a return to preintervention pulse-at-rest values. The research examined the treadmill training method and found that it can be operated with the support of an unskilled staff person under the supervision of a physiotherapist. The research was performed under real-life conditions, enabling relatively easy implementation in the existing conditions of special education centers. This method is a type of exercise that is easy to operate without entailing long-term budgetary expenses and might improve the health status of children with ID, who are a population at risk for developing heart-related diseases at a young age.